GLASIR PADA KERAMIK SINGKAWANG: TEKNOLOGI DAN SENI KERAMIK AWAL ABAD KE- 20 M - Wicaksono, Honami Mulan Andadari (Multikultura, 2026)
This article discusses the use of glaze on Singkawang ceramics in the early 20th century as a reflection of technological and artistic developments among the artisan community in Singkawang, West Kalimantan. Through a literature review, this study highlights how glazing techniques, involving the selection of materials, coating processes, and high-temperature firing, became an important part of Singkawang ceramic production. The use of Tungku Naga kilns and firing traditions influenced by East Asian technology indicate local adaptation and development. The results of the study show that glaze not only functions as a protective coating, but also enriches the aesthetic value and cultural identity of Singkawang since the early 20th century.